The Effect of Corporate Governance and Profitability on Firm Value Mediated by Corporate Social Responsibility (CSR) Disclosure in Infrastructure, Utility, and Transportation Sector Companies Listed on the Indonesia Stock Exchange (IDX) - Melya, Liza; Sakir, Faisal, A (International Journal of Scientific Research and Management (IJSRM), 2024)
This study examines the corporate governance and profitability effect on firm value with Corporate Social Responsibility (CSR) disclosure as mediation in infrastructure, utilities, and transportation sector companies listed on the Indonesia Stock Exchange (IDX) for 2018-2022. To test the direct and indirect effects of factors affecting firm value, SEM-PLS analysis was used. The study discovered that corporate governance and CSR positively impact firm value. However, profitability does not have a significant effect on firm value. Additionally, corporate governance and profitability both have a positive influence on CSR. CSR can partially mediate the effect of corporate governance on firm value, and fully mediate the effect of profitability on firm value. The most commonly implemented aspects of CSR, based on Global Reporting Initiative (GRI) disclosure, are social, environmental, and economic, in that order. The findings suggest that companies that prioritize CSR, particularly environmental aspects, are more attractive to investors.